Predicting iliac bone marrow harvest success in osteonecrosis of femoral head using preoperative bone scintigraphy uptake: a cross sectional study - Yohei Tomaru; Yasuhiro Homma; Philippe Hernigou; Tomokazu Yoshioka; Hisashi Sugaya; Yuta Tsukagoshi; Hiroshi Kamada; Hajime Mishima (BMC Musculoskeletal Disorders)
Abstract Background Bone marrow transplantation has been employed as a regenerative treatment for osteonecrosis of the femoral head (ONFH). However, in clinical practice, obtaining a sufficient volume of bone marrow aspirate under general anesthesia can sometimes be challenging. Currently, there is no established method to predict the quantity and quality of bone marrow that can be harvested preoperatively. We hypothesized that these parameters could be inferred from preoperative bone scintigraphy uptake. Therefore, this study aims to investigate the relationship between bone marrow quantity and quality and the uptake observed on preoperative bone scintigraphy. Methods This retrospective study included 145 consecutive patients with ONFH who underwent bone marrow transplantation between 2009 and 2014. The edges of the ilium were manually delineated on the images obtained by combining bone scintigraphy and computed tomography. The average pixel value within this delineated area was calculated. We analyzed correlations between the average pixel value on bone scintigraphy for both ilium and the quantity of bone marrow collected from the ilium, as well as the CFU-Fs obtained from 600μl of concentrated bone marrow. Results Sixty-two patients were excluded due to insufficient data on bone scintigraphy and colony-forming unit of fibroblasts (CFU-Fs), leaving 83 patients for final analysis. The mean bone marrow quantity, CFU-Fs per 600μl, and the pixel value of bone scintigraphy were 227 ml (range, 6–400), 42 (range, 4–200), and 109 (range, 28–730), respectively. A significant correlation was found between the pixel value and bone marrow quantity (Pearson’s correlation coefficient, r = 0.24, p < 0.05), while no significant relationship was observed with CFU-Fs. Conclusions Patients with low bone scintigraphy uptake require careful consideration as an adequate amount of bone marrow may not be obtainable.